China's Hong Kong : A Political and Cultural Perspective - Jiang, Shigong (Springer Singapore : Imprint: Springer, 2017)
This book differs from most others of its kind, by looking at the Hong Kong issue from China's perspective, which in turn mirrors China's own situation. Through a legal lens, the author conducts a political and cultural examination of the past and the present, and provides a comprehensive overview of the many theories and problems concerning Hong Kong. Including reflections on the theory of administrative absorption of politics, a historical review of "one country, two systems" and an analysis of the form and nature of the Basic Law, it offers a valuable reference resource for studying the historical, political and legal context of Hong Kong under the principle of "one country, two systems". Instead of over-simplifying the issue of Hong Kong or only seeing it as a Chinese regional issue, the book regards it as a central Chinese issue and the key to understanding China.
Keywords: Social sciences.; Political philosophy.; Area studies.; elektronické knihy; electronic books